Characterisation of efficiency losses in ground source heat pump systems equipped with a double parallel stage: A case study. (March 2020) - García-Céspedes, J.; Arnó, G.; Herms, I.; de Felipe, J.J.
Abstract: This work focuses on methods to characterise the efficiency losses in existing ground-source heat pump (GSHP) installations under part-load conditions. Efficiency losses were identified and quantified in a GSHP by analysing key parameters measured and recorded by its monitoring system. The heating/cooling production facility comprises a vertical borehole heat exchanger field and a GSHP equipped with a double parallel stage and fixed-speed compressors within. The methodology was based on the EN-14825 standard and other recent works. However, the particularity of having two parallel stages motivated the creation of a modified theoretical approach, since the original methodology was only applicable to single-stage heat pumps. To obtain significant results, minute-resolved data acquired over time periods with almost constant thermal load (quasi-steady state conditions) proved necessary. The study concluded that the coefficient of performance can suffer reductions as high as 9% exclusively due to part-load operation. Most importantly, it demonstrated that the actual capacity of the GSHP as a whole shows an effective reduction ranging between 20% and 24% with respect to the declared capacity of the heat pump alone. Moreover, weekly-averaged data collected during 3 complete cool and warm seasons point to a progressive degradation from the date of commissioning. Finally, Ground Loop Design software (v2016) was used to validate the methodology. Consistent agreement was found between simulated and measured seasonal performance. Highlights: Study of efficiency losses in GSHPs operating under real, part-load conditions. Theoretical approach adapted to double parallel stage with fixed-speed compressors. Methodology based on correlation between part-load factor and part-load ratio. Minute-resolved data acquisition is the key towards a consistent analysis. Simulated seasonal performance validates methodology.